Cy Twombly's seasons, in the shadow of Renoir - Marta Mitjans Puebla (Ignatianum University Press, 2020)
The iconographical analysis of Four seasons (1993), by the contemporary artist Edwin Parker "Cy" Twombly (Cy Twombly, 1928 - 2011) must be understood considering the importance of one of the most famous impressionist painters: Pierre-Auguste Renoir (1841 - 1919). La vague (1879) and Paysage bords de Seine (1879) are two oil on canvas where Renoir prints the feeling of captivating the ephemeral through the colour and the movement of light. Four seasons has its roots in American lyrical abstraction. The need of making a portrait of lightness, through a creation where image and text are together, represents the evolution of Renoir's work in contemporary art. As an impressionist artist, Renoir describes beauty as the reflection of the harmony of the world, as such as a bridge between aesthetic and emotional education. With this proposal, Cy Twombly sublimates the idea of beauty in contemporary art.